CV RISK – A new relative cardiovascular risk score. (November 2019) - Zdrenghea, Dumitru; Guşetu, Gabriel; Zdrenghea, Mihnea; Cismaru, Gabriel; Caloian, Bogdan; Vaidean, Georgeta; Pop, Dana
Abstract: Background and aims: Nowadays it is recommended to use risk scores to evaluate the magnitude of cardiovascular risk in healthy people, most popular being SCORE (Europe) and Framingham and ASCVD (US). Unfortunately, they are not enough motivating in young and old population, don't consider protective factors and cannot be used in cardiovascular patients always included in very high risk category. To improve the evaluation everytime of individual cardiovascular risk we described a new score – CVRISK (cardiovascular relative individual risk). Methods: It uses 15 items and can be used also in cardiovascular patients. The first seven items are clinical – age and gender, heredity, smoking, hypertension, obesity, psychosocial stress, previous cardiovascular disease. For items refer to laboratory data – LDL-C, HDL-C, TG, fasting plasma glucose (diabetes mellitus). The last two are protective factors – physical activity and healthy diet. Results: Every item has a number of risk points and protective factors decrease with 25% and 15% the calculated risk. The risk can be automatically calculated after the introduction of the required data through an algorithm available at www.cvrisk.ro . Here, the calculated risk is compared with optimal and maximal risk. Thus the user is motivated to initiate or to continue preventive measures also suggested at www.cvrisk.ro, to improve cardiovascular health. Conclusion: CVRISK is not a substitute of current risk scores, but a complimentary tool to appreciate and modulate the individual cardiovascular risk. It can be useful to prevent CV disease or to improve its evolution. Individuals themselves can calculate it in order to maintain or improve their health.